Making social and historical sense: A Confucian-phenomenological dialogue - Sigurðsson, Geir (Acta Orientalia Vilnensia, 2007)
A meaningful comparison between Western and Eastern philosophical thought demands that not only similarities but also divergences be brought to light. This may facilitate the appreciation of culturally divergent philosophical traditions but no less open up further possibilities for profiting from the different routes taken. Some seminal thinkers from the Western phenomenological tradition, notably Martin Heidegger and Hans-Georg Gadamer, have come to understand that their philosophical dispositions seem to converge with important themes and approaches in Asian philosophy. This paper attempts to open a Confucian-phenomenological dialogue by discussing some noteworthy parallels between the traditions, but also by arguing that their contrary tendencies to understand the relationship between sagehood or, indeed, philosophy, and lived human reality lead them onto vastly different paths. The paper concludes with the argument that Western thinkers have much to gain by more serious exploration of the Confucian preference for wisdom acquired through historically informed identities and everyday communal human living.
Keywords: -